Tukad Unda Development: From a Viral Tourism Object to A Center for Future Bali Civilization Plan - Rizky Januar (Bali Tourism Board, 2022)
Tukad Unda is a volcanic-formed river with areas for drainage and deposition of lava material resulting from volcanic eruptions. The area covers the Karangasem Regency in the upstream and Klungkung Regency in the downstream parts. In the Balinese language, Tukad means river, and Unda means terraced. Hence, Tukad Unda means terraced river. The obvious point is that Tukad Unda flows through a dam with two overlapping terraces. Thus, the flowing water forms a level resembling a mini waterfall. The place is one of a kind for those who enjoy calm and breezy nature. Besides having clear water with schools of small fish, the area is also surrounded by soothing trees. Tourists can either stop by the available restaurants or play in the water. The water barrage of Tukad Unda has become a tourist destination that attracted much attention from visitors in recent years. Its serene, lush natural atmosphere, gurgling water, and a curtain waterfall on the dam wall showcase a relieving experience in downtown Klungkung. Tourists can now comfortably visit the Tukad Unda dam area since the local village has managed the area as a complete tourist destination with various supporting facilities. However, Tukad Unda is a river prone to mud flooding, especially when Mount Agung experiences increased volcanic activity. Thus, the central and local governments focus on developing supporting facilities to strengthen the Tukad Unda utilization. In addition, many studies show the potential of the Tukad Unda, along with its watershed, which, when properly developed and managed, can significantly impact the welfare of the surrounding community.